Blockchain Based Aadhaar Security - P.J, Sankaranarayanan; George, Geogen (International Journal of Engineering and Technology, 2018)
A blockchain is a decentralized, disseminated and digital ledger that can’t be altered retroactively without modifying every single blocks and the consensus of the network. Blockchain can be used in smart contracts, Banks, IoT devices, Database management, etc., Due to recent times flaws and leakage of Aadhaar information (Aadhaar which is the largest government databases of the Indian citizens) in Internet the security and privacy of Aadhaar became questionable. In order to ensure the security of Aadhaar, Blockchain has the potential to overcome security and privacy challenges in Aadhaar. In this project we are going to create a Blockchain for Aadhaar database and implement light weight algorithm for efficiency, optimization and scalability along with the Blockchain securing algorithm.